(untitled) (Research, Society and Development, 2022)
The “Programa Navega Saberes Cine child labor (CineTi)” is an extension project that aims to promote reflections on the rights of children and adolescents and the practice of child labor in order to promote multipliers on this knowledge. Over the course of 1 year, surveys were carried out with a descriptive design and with a quantitative data collection that seeks to investigate the perceptions that Instagram users have about child labor. As a result, the reality of child labor was verified in 68% who reported that they knew someone who had suffered child labor. It is concluded that Instagram was an important tool to continue the activities of the extension project at the University during the Covid-19 pandemic period, and allowed a considerable reach of people and faster communication responses.